The Youth Guarantee, Vulnerability, and Social Exclusion Among NEETs in Southern Europe - Niall O'Higgins; Kate Brockie (Politics and Governance, 2024)
Young people neither in employment, education, or training (NEETs) are particularly vulnerable to social and economic exclusion. Indeed, recognition of this fact was a key motivating factor underlying the development of the Youth Guarantee. This article uses data from the EU Labour Force Survey and EU Statistics on Income and Living Conditions to examine how the characteristics of the NEET population and their associated vulnerability to social exclusion vary across different sub-groups of young NEETs and how this has changed in Italy, Portugal, and Spain since 2015. The analysis focuses on the determinants of NEET status, youth vulnerability to poverty and social exclusion, and also examines the propensity of young NEETs to engage with public employment services in order to assess the extent to which young people most at risk of social exclusion are within the purview of the Youth Guarantee’s activities. The article highlights how the composition and vulnerability of young NEETs have altered between 2015 and 2021. While the risks of poverty and social exclusion of long-term unemployed NEETs have remained unchanged since 2015, the vulnerability of the most at-risk subgroup of young people, those who are NEET due to family responsibilities, has become more pronounced. Moreover, the engagement with public employment services of the most at-risk NEET sub-groups has remained persistently low. The findings suggest that greater efforts are needed to remove the obstacles to labour market re-integration faced by the most vulnerable groups within the purview of the programme and, above all, young women with family responsibilities.